Issue of Virtual Currency by the Central Bank: Monetary Policy and Legal-Economic Aspects in Recent Experience (Global Journal of Human-Social Science, 2023)
Indeed central bank digital currency issues is a no return way International experiences on assessing this possibility have been increasing mainly on designing devices for future purposes and also demonstrate deep concern with this issue Based on macroeconomic models this paper aims to discuss how central bank digital currency issues impact monetary policy and how regulation has coped with this still unknown innovation Furthermore it is also our aim to discuss if a recent Brazilian regulation law takes appropriately virtual money issues into account
Keywords: virtual money; monetary policy and regulation